Modelamiento de los aisladores de la línea de 69kv Mulalo - la Cocha mediante análisis de elementos finitos, para determinar las fugas de corriente y su relación con el ensayo de ultrasonido a causa de condiciones de perdida de rigidez dieléctrica. - Herrera Naranjo, Estalin Gonzalo (2023)
The present research consisted of simulating the insulators of the 69 kV Mulaló - La Cocha line through finite element analysis, to determine current leakage and its relationship with the ultrasound test due to conditions of loss of dielectric strength. For which field tests are carried out such as visual inspection, ultrasound and thermography. The applied methodology consisted of a field study through the use of technological equipment to determine the state of the insulators and the environmental conditions, in which pollution incrustation and fissures were found, that with the thermography equipment is observed that in the phase R maintains a temperature of 76C that shows an electrical tracking of high frequencies and amplitudes that is out of the conditions to be intervened in immediate maintenance, in phase S a temperature of 44.8C with a stable ultrasound tracking under normal conditions and in phase T, a temperature of 59C with irregular ultrasound frequencies is therefore recommended to make an immediate change. According to the modeling with the FEMM software, the dynamic evaluation was carried out where in Phase R there is a current leakage of 30 A/m2, in phase S a leakage of 3.2 A/m2 and in T a leakage of 200 A/m2. m2. The same one that determines that there is a relationship between the current leakage and the superficial deterioration of the insulators and an increase in the frequency and amplitude of the ultrasound test.